The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/jaa.s334752
|View full text |Cite|
|
Sign up to set email alerts
|

The Multiomics Analyses of Gut Microbiota, Urine Metabolome and Plasma Proteome Revealed Significant Changes in Allergy Featured with Indole Derivatives of Tryptophan

Abstract: Objective To explore changes in the gut microbiota (GM), urine metabolome and plasma proteome in individuals with allergies using multiomics analyses, and identify the key components and mechanism. Methods This was a cross-sectional study. All subjects were recruited to collect fecal, urine and blood samples. 16S rDNA sequencing was used to analyze the structure and function of the GM, liquid chromatography mass spectrometry was used to quantify metabolites in the urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Our results of the reduced TSLP expression and the alleviation of AD after 7 days of the treatment are consistent with the previous reports of locally applied inole-derivatives which partially alleviated the skin inflammation and inhibited the TSLP formation in keratinocytes [ 29 ]. In previous reports, when macrophages that are differentiated from THP-1 cell lines were stimulated with LPS, IBA significantly inhibited the LPS-induced upregulation of IL-4 and IL-6 mRNA, and I3LA inhibited the expression of IL-6 mRNA [ 26 ]. Our results also showed that I3LA suppresses the IL-6 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results of the reduced TSLP expression and the alleviation of AD after 7 days of the treatment are consistent with the previous reports of locally applied inole-derivatives which partially alleviated the skin inflammation and inhibited the TSLP formation in keratinocytes [ 29 ]. In previous reports, when macrophages that are differentiated from THP-1 cell lines were stimulated with LPS, IBA significantly inhibited the LPS-induced upregulation of IL-4 and IL-6 mRNA, and I3LA inhibited the expression of IL-6 mRNA [ 26 ]. Our results also showed that I3LA suppresses the IL-6 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…I3LA was effective in regulating the STAT1 signaling pathway [ 31 ]. In a previous study, the macrophages that were differentiated from THP-1 cell lines were stimulated with lipopolysaccharide (LPS) to confirm the effect of an indole derivative on the expression of IL-4, IL-6, and IL-13, which validated that indole-3-butyric acid (IBA) and I3LA play a role in allergic pathogenesis [ 26 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, hypersensitivity reactions are associated with specific Trp metabolite alteration. Allergic subjects have decreased levels of indole-3-butyric and indole-3-lactic acids [ 103 ]. Additionally, new reports show that direct administration of some Trp metabolites can be useful in the management of delayed-type hypersensitivity [ 104 ].…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%
“…Proteomic technology is an efficient tool for identifying potential biomarkers associated with pathological states [ 19 , 20 ]. With the rapid development of mass spectrometry (MS), proteomics can be used to accurately profile global proteomic alterations in various cells, tissues and body fluids.…”
Section: Introductionmentioning
confidence: 99%